Zimdancehall Music as Rules of Sexual Engagement - Mangeya, Hugh (Palgrave Macmillan, 2022)
The chapter argues that Zimdancehall music can be read as a discourse laying the ‘rules of engagement’ for normative heterosexual encounters. Sexual intercourse is an important arena on which gender relations are performed. Music can provide important insights into how power relations are enacted during the sexual act. It is therefore imperative to unpack the dominant images and metaphors used by Zimdancehall artists to represent the ‘ideal’ or ‘perfect’ pleasurable sexual experience. Using critical discourse analysis as an analytical framework, the chapter argues that sexual intercourse is much more than the ‘innocent’ intimate interaction between two individuals. Rather, sexual encounters are power-driven transactions in which the goal is total domination. Issues relating to ‘roughness’, infliction of pain, duration and total surrender, among others, are critical in determining the success of the sexual encounter. This is critical particularly in exposing otherwise taken-for-granted forms of gender-based violence that may continue to go unnoticed and/or unchecked. Songs for analysis were selected through purposive sampling in which songs that speak to the sexual encounter were considered.